Answer:
i don' think you can
Step-by-step explanation:
Answer:
a
Step-by-step explanation:
Answer:
10 units
Step-by-step explanation:
To find the length we can use the formula
d = sqrt( (y2-y1)^2 + (x2-x1)^2)
We have the two points (-5,5) and (3,-1)
d = sqrt( (-1-5)^2 + (3--5)^2)
d = sqrt( (-6)^2 + (3+5)^2)
d = sqrt( (-6)^2 + (8)^2)
d = sqrt( 36 + 64)
d = sqrt(100)
d = 10
Answer:
C. (-3,11)
Step-by-step explanation:
Tp is (-3,6) implies the quadratic could have been
f(x) = (x+3)²+6
(2/3)f(x) = (2/3)[(x+3)²+6]
= (2/3)(x+3)²+4
(2/3)f(x)+3 = (2/3)(x+3)²+4+3
= (2/3)(x+3)²+7
Tp at (-3,7)
Alternately,
No change in domain so x remains-3
(2/3)f(x) changes y from 6 to 4 (6×2/3)
+3 increases the y by 3
i.e 4+3 = 7
So, (-3,7)